Relaxation Methods To Reduce Pain And Injuries SEFT Post Sectio Caesaria - Sugih Wijayati; Ngadiyono Ngadiyono; Triana Sri Hardjanti (Jurnal Riset Kesehatan, 2013)
Various ways are used to eliminate or reduce pain during childbirth with spontaneous or with Sectio Caesarian birth using non-pharmacological and pharmacological. Approaches one intervention that can be done through non-pharmacological approach by midwives is throug with relaxation and spiritual emotional freedom tecnique(SEFT) methods.The purpose of this study was is to investigate the different methods of relaxation and SEFT to decrease pain intensity because Sectio Caesaria Operation at Semarang District Hospital and Dr.Adyatma,MPH Hospital in Semarang City.The design used was is pre experimental design, posttest only design with control group design with time spent crosssectional approach.The results shown of significant differences method of relaxation and SEFT to decrease level of pain (pain value) because Sectio Caesaria Operation. It is shown the average respondent without any pain and SEFT relaxation method at 5,60 and the average respondent pain with relaxation methods and SEFT of 4,13. There is a decrease in the mean or average - average labor pain 1,47and p valueof 0.004.